The international dictionary of artificial intelligence - Raynor, William J. (Chicago ; London : Glenlake Pub. Co. ; Fitzroy Dearborn Pub., 1999)
Anticipating the needs of professionals, researchers, and students alike, International Dictionary of Artificial Intelligence defines and illustrates over 2,500 terms and provides detailed explanations of major concepts as well as topics in related disciplines. The Dictionary also contains an annotated bibliography and an extensive appendix of World Wide Web sites devoted to the latest trends and developments in the world of artificial intelligence.
ne 24/08/2021
Ref.
Keywords: Artificial intelligence